Reassessment of Annamocarya sinesis (Carya sinensis) Taxonomy through Concatenation and Coalescence Phylogenetic Analysis - Jie Luo; Junhao Chen; Wenlei Guo; Zhengfu Yang; Kean-Jin Lim; Zhengjia Wang (Plants, 2021)
Due to its peculiar morphological characteristics, there is dispute as to whether the genus of Annamocarya sinensis, a species of Juglandaceae, is Annamocarya or Carya. Most morphologists believe it should be distinguished from the Carya genus while genomicists suggest that A. sinensis belongs to the Carya genus. To explore the taxonomic status of A. sinensis using chloroplast genes, we collected chloroplast genomes of 16 plant species and assembled chloroplast genomes of 10 unpublished Carya species. We analyzed all 26 species’ chloroplast genomes through two analytical approaches (concatenation and coalescence), using the entire and unique chloroplast coding sequence (CDS) and entire and protein sequences. Our results indicate that the analysis of the CDS and protein sequences or unique CDS and unique protein sequence of chloroplast genomes shows that A. sinensis indeed belongs to the Carya genus. In addition, our analysis shows that, compared to single chloroplast genes, the phylogeny trees constructed using numerous genes showed higher consistency. Moreover, the phylogenetic analysis calculated with the coalescence method and unique gene sequences was more robust than that done with the concatenation method, particularly for analyzing phylogenetically controversial species. Through the analysis, our results concluded that A. sinensis should be called C. sinensis.